An Investigation on I-V Characteristic for CMOS PIN Photodiode: Variable I-Layer - Othman, Mohd Azlishah; Mohammed Napiah, Zul Atfyi Fauzan; Ismail, Mohd Muzafar; Sulaiman, Hamzah Asyrani; Misran, Mohamad Harris; Meor Said, Maizatul Alice (2012)
In this paper presented an investigation on I-V characteristic for CMOS PIN Photodiode. PIN diodes are widely used in optics and microwave circuits as it acts as a current controlled resistor at these frequencies. PIN diode performance is greatly influenced by the geometrical size of the device, especially in the intrinsic region. Two different I-layer thickness of PIN diode structure has been designed using Sentaurus Technology Computer Aided Design (TCAD) tools. The I-layer thickness (or width) is varied from 4 µm to 8 µm in order to investigate its effects on the current-voltage (I-V) characteristics. These structures were design based on CMOS process. Keyword - PIN Photodiode, Silvaco TCAD, IV Characteristic, Reverse Bias.